Hyperphenylalaninemias genotyping: Results of over 60 years of history in Lombardy, Italy. Issue 2 (19th December 2022) - Rovelli, Valentina; Cefalo, Graziella; Ercoli, Vittoria; Zuvadelli, Juri; Olivia, Turri; Graziani, Daniela; Luisella, Alberti; Bassi, Davide; Re Dionigi, Alice; Selmi, Raed; Paci, Sabrina; Salvatici, Elisabetta; et al.
Abstract: Background: Hyperphenylalaninemias (HPA) are due to several gene mutations, of which the PAH gene is the most frequently involved. Prevalence and incidence of disease vary between populations, with genotype/phenotype correlations not always capable to correctly predict disease severity. The aim of this study was to give an overview of PAH mutations among one of the largest cohort of patients among Europe, born in Lombardy (Italy) starting from late 1970 s and including over a 60 years of activity; furthermore, to evaluate and discuss identified genotype/phenotype correlations and related reliability. Patients/Methods: Eight hundred and twenty‐six HPA patients in current follow‐up at the San Paolo Hospital in Milan (Italy) were retrospectively reviewed, including molecular results and allelic phenotype and genotype values (attributed on the basis of the APV/GPV system) to verify genotype–phenotype correlations. Results: A total of 166 different PAH variants were reviewed; of those, seven variants were identified as not previously described in literature. Most frequently reported variant was p.Ala403Val, followed by p.Arg261Gln, p.Val245Ala, IVS10‐11 g>a, p.Tyr414Cys and p.Leu48Ser. Phenotype prediction, based on APV/GPV, matched the actual phenotype in most cases, but not always. Conclusion/Discussion: The cohort of patients included in this study constitute a representative sample of the HPA population worldwide. Studies on this sample may allow to improve clinical and genetic evaluation performances for affected patients, consequently to develop personalized medicine interventions and provide more precise indications on the correct treatment approach based on the accumulated evidence, also in light of a prognostically reliable but not always conclusive APV/GPV system. Abstract : An overview of PAH mutations among one of the largest cohort of patients among Europe to evaluate and discuss identified genotype/phenotype correlations and related reliability. APV/GPV system is a prognostically reliable but not always conclusive system.